Antioxidant Activities and Bioactive Compound in The Extract of Lobophytum sp. - Andi Mu'nisa Syamsu (Fakultas MIPA UNM, 2023)
This study is a descriptive exploratory research that aims to know the activity of soft coral Lobophytum sp. extract as an antioxidant. Sample extraction was done by maceration using methanol. Viscous extract obtained was then partitioned using n-hexane until gained methanol and n-hexane fraction. The chemical compositions of the methanol extract of Lobophytum sp were investigated using Gas chromatography-Mass spectrometry. The yield result of soft coral Lobophytum sp. extract is 2,59%. The weight of extract partition result were methanol fraction 8,76 g and n-hexane fraction 1,02 g. Antioxidant activity test using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assay. Ascorbic acid was also used as positive antioxidant control. The percentage of inhibition and IC50 were measured. Antioxidant activity test which gains the best antioxidant activity is methanol fraction then followed by n-hexane fraction, both showed DPPH free radical 50% can be inhibited the activity with IC50 rate in a sequence 16,93 ppm and 30,93 ppm. GC-MS analysis, 50 kinds of chemical composition are identified in the Lobophytum sp. The results showed that the soft coral extracts of Lobophytum sp. has antioxidant activity.Keywords: soft coral (Lobophytum sp), GC-MS, fractions metahol and hexane